2021
DOI: 10.21037/gs-21-770
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant pyrotinib plus nab-paclitaxel, doxorubicin, and cyclophosphamide for HER2-positive locally advanced breast cancer: a retrospective case-series study

Abstract: Background: The anti-tumor activity of pyrotinib has been confirmed in human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer. This study investigated the effect of pyrotinib plus nabpaclitaxel, doxorubicin, and cyclophosphamide as neoadjuvant therapy in patients with HER2-positive locally advanced breast cancer.Methods: In this single-center retrospective study, female patients with HER2-positive locally advanced breast cancer received pyrotinib 320 mg orally once a day and the TAC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…Consequently, up to 96% of patients with diarrhea treated with second-generation TKIs are assumed to have direct mucosal atrophy and injury caused by the inhibition of ErbB signaling within the intestinal epithelia (32,33). The results from the analysis of the present study revealed that gastrointestinal reactions, as well as myelosuppression, are the most common adverse events of any Grade and also Grade ≥3, which was consistent with other retrospective studies (34)(35)(36)(37). It is worth noting that nearly half of the participants in the present analysis experienced Grade 3 diarrhea, with a significantly higher incidence compared with capecitabine combination therapy in advanced or metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consequently, up to 96% of patients with diarrhea treated with second-generation TKIs are assumed to have direct mucosal atrophy and injury caused by the inhibition of ErbB signaling within the intestinal epithelia (32,33). The results from the analysis of the present study revealed that gastrointestinal reactions, as well as myelosuppression, are the most common adverse events of any Grade and also Grade ≥3, which was consistent with other retrospective studies (34)(35)(36)(37). It is worth noting that nearly half of the participants in the present analysis experienced Grade 3 diarrhea, with a significantly higher incidence compared with capecitabine combination therapy in advanced or metastatic breast cancer.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, 207 out of 395 patients who received pyrotinib-containing neoadjuvant therapy achieved pCR (defined as the proportion of patients who achieved a complete response or partial response), and the objective response rate was close to 100% across all five studies. Real-world studies have confirmed the activity of pyrotinib in the neoadjuvant setting (34)(35)(36)(37). Owing to discrepancies in inclusion criteria, drug dosage and duration of therapy, optimal dosing of pyrotinib in combination with chemotherapy remains unknown and must be further explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, pyrotinib-related diarrhea was the most frequent AE, whereas the overall safety profile in the present study was acceptable. The incidence of grade ≥3 diarrhea in this study was much lower than that of previously reported pyrotinib-containing neoadjuvant therapy (6.5% vs. 18.2–64.5%) ( 13 - 15 , 29 ). The use of a single HER2-targeted agent and a single chemo-drug in the neoadjuvant setting might have contributed to the low incidence of severe diarrhea.…”
Section: Discussioncontrasting
confidence: 80%
“…Recently, various combinations of pyrotinib plus chemotherapy for HER2 + BC in the neoadjuvant setting have been increasingly explored. Several phase II trials showed that dual-target therapy with trastuzumab and pyrotinib plus neoadjuvant chemotherapy (NAC) exhibited pCR rates between 51.6% and 73.7% ( 13 , 15 , 29 , 30 ). A real-world analysis found that the tpCR rate of pyrotinib-containing neoadjuvant therapy was 48.5%, respectively ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have presented that receiving radiotherapy and chemotherapy after surgery has significant clinical value in improving the prognosis of patients ( 26 , 44 ). Recently, neo-adjuvant chemotherapy has gradually become the first choice of systemic therapy for TNBC, especially for those who have locally advanced tumors ( 45 , 46 ). Neoadjuvant chemotherapy remarkably has been shown to improve the prognosis of the patients who received neo-adjuvant chemotherapy before surgery and achieved pathologic complete response during surgery ( 47 ).…”
Section: Discussionmentioning
confidence: 99%